On the Genealogy of the Modern Experience of Consciousness. Christian Self-Examination - Wawrzyniak, Szymon (Hybris, 2022)
The article aims to investigate the modern self-experience of an individual from the point of view of the historical conditions that make this experience possible. This undertaking will be supported by the turn to a theory and practice of self-examination as it appears in early Christianity. It is widely recognized that there is a connection between modernity and subjectivity. One of the areas where it is reflected is philosophy. By founding the paradigm of modern philosophy, Descartes finds in his turn to himself a certain basis of cognition and a space where forward progress in the process of building a new system of knowledge may take effect. For Descartes consciousness is, however, a means, not an end. This is one of the reasons why it is not "questioned" sufficiently. Among many questions that were not addressed at all for a long time, one should mention, how the experience on which Descartes bases his reasoning became possible. In the history preceding the Cartesian turn inward, we can identify many interesting moments - which can be found with great confirmation in early Christianity - that play a significant role in the constitution of the experience that will become so important for modernity.